PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH MENGGUNAKANAUDIO VISUAL BERBASIS PERISTIWA SEJARAH LOKAL DI MADIUN - Amalia, Titin Rahmawati; Wasino, W.; Suryani, Nunuk (Sebelas Maret University (UNS), 2016)
The rapidly growing technology affects all aspects of life, one of which is education. Good learning media can facilitate teachers in presenting the material in the learning process. It also can increase the interest in learning that have an impact on learning achievement. The purpose of this study is to describe the use of instructional media history in SMP Negeri 2 Jiwan Madison County, develop learning media-based audio-visual history of using local events in Madiun, and assess the effectiveness of instructional media-based audio-visual history of using local historical events in Madison.This research is the development of research development procedures adapted from Borg & Gall. Location research in SMP N 2 Jiwan Madison County. Data collection techniques by means of interviews, observations, questionnaires, and tests. Data were analyzed using descriptive qualitative and quantitative.Results: 1) social studies teacher at SMP N 2 Jiwan, Madison County is still using conventional methods by means of lectures and question and answer and have not used the medium of learning; 2) Learning media developed using ADDIE instructional design of Molenda which consists of five stages: analisys, ie analyzing the needs of instructional media; design, namely collecting and designing instructional media; development, namely preparing instructional media using windows movie maker software, then testing the product internally; implementation, for example, applying the media in the learning process; and evaluation, which tested the effectiveness of the product. Instructional media developed rated as good by a material with an average score of 3.53; considered sufficient by media experts with an average score of 3.31; and assessed both by expert instructional design with an average score of 3.69; 3) The effectiveness of instructional media through t test. From the results obtained t_hitung t test = 4.6> 1.96 = t_tabel because t_hitung> t_tabel then H_0 rejected. Means that both groups have unequal learning achievement. The mean learning achievement using instructional media group developed = 85> mean learning achievement groups using power point = 66.67, and therefore concluded that the group using audio-visual media have a better learning performance than the use of media power point, so that the audio-visual instructional media developed is considered effective in the learning process.